Reaping The Whirlwind: The Impact of Parental Smoking Habits on Children's Education - Madonna Simatupang; Kyohei Yamada (The Journal of Indonesia Sustainable Development Planning, 2025)
While parental smoking is widely linked to negative health and developmental consequences for children, its long-term influence on educational outcomes has received relatively little attention. This study investigates how parents’ smoking behaviors affect the number of years children spend in school, providing important evidence for policymaking in Indonesia to support human capital development. Using panel data from Waves 3 and 5 of the Indonesian Family Life Survey (IFLS) and a fixed-effects model, results show a persistent negative association between parental smoking and children’s educational outcomes. Maternal smoking exhibits a similar direction and magnitude of effect as paternal smoking, but is not statistically significant, possibly due to compensatory parental attitudes toward education. These findings highlight the need for comprehensive policies, including higher tobacco taxes, stricter household smoking regulations, stronger enforcement of school attendance, and equitable access to educational infrastructure.